Laparoscopic One Anastomosis Gastric Bypass as a Revisional Procedure After Failed Vertical Banded Gastroplasty: Our Center Experience - Hosam Elghadban; Ashraf Shoma; Emad Abdallah; Ahmed Negm; Elsayed Abdullah; Hossam Hamed; Sameh Ghareeb; Ahmed Lotfy; Ahmed Taki-Eldin (Journal of Obesity)
Conclusions: OAGB is a feasible and effective revisional procedure after failed open VBG. However, the risk of bile reflux should be considered to justify these findings; further prospective randomized controlled trials are required.